Młodzi ludzie w krainie szczęśliwości = Young people in the land of happiness - Sińczuch, Marcin (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses the place of young people in society. Happiness is an indicator of the factual social position of youth as a group. It is difficult to be happy while being permanently conflicted with society and impossible to feel life satisfaction while one?s basic needs for interpersonal relationships or for adequate life standards are not met. In this way, the measures of happiness among young people in Poland after the transition in 1990 become the measures of their place in society. They inform the society itself to what extent it has been able to create favourable conditions for the development of future generations.
Keywords: młodzież; poczucie szczęścia; pozycja społeczna; miejsce w społeczeństwie; youth; happiness; social position; place in society